TLR4 accessory molecule RP105 (CD180) regulates monocyte-driven arteriogenesis in a murine hind limb ischemia model. - Antonius J N M Bastiaansen (Public Library of Science (PLoS), 2014)
Aims We investigated the role of the TLR4-accessory molecule RP105 (CD180) in post-ischemic neovascularization, i.e. arteriogenesis and angiogenesis. TLR4-mediated activation of pro-inflammatory Ly6Chi monocytes is crucial for effective neovascularization. Immunohistochemical analyses revealed that RP105+ monocytes are present in the perivascular space of remodeling collateral arterioles. As RP105 inhibits TLR4 signaling, we hypothesized that RP105 deficiency would lead to an unrestrained TLR4-mediated inflammatory response and hence to enhanced blood flow recovery after ischemia. Methods and results RP105-/- and wild type (WT) mice were subjected to hind limb ischemia and blood flow recovery was followed by Laser Doppler Perfusion Imaging. Surprisingly, we found that blood flow recovery was severely impaired in RP105-/- mice. Immunohistochemistry showed that arteriogenesis was reduced in these mice compared to the WT. However, both in vivo and ex vivo analyses showed that circulatory pro-arteriogenic Ly6Chi monocytes were more readily activated in RP105-/- mice. FACS analyses showed that Ly6Chi monocytes became activated and migrated to the affected muscle tissues in WT mice following induction of hind limb ischemia. Although Ly6Chi monocytes were readily activated in RP105-/- mice, migration into the ischemic tissues was hampered and instead, Ly6Chi monocytes accumulated in their storage compartments, bone marrow and spleen, in RP105-/- mice. Conclusions RP105 deficiency results in an unrestrained inflammatory response and monocyte over-activation, most likely due to the lack of TLR4 regulation. Inappropriate, premature systemic activation of pro-inflammatory Ly6Chi monocytes results in reduced infiltration of Ly6Chi monocytes in ischemic tissues and in impaired blood flow recovery.